Examining early adolescents' motivation for physical education: associations with actual and perceived motor competence. (4th July 2021) - Estevan, Isaac; Bardid, Farid; Utesch, Till; Menescardi, Cristina; Barnett, Lisa M.; Castillo, Isabel
ABSTRACT: Background: The dynamic nature of physical education (PE) requires careful consideration of lesson planning and delivery in order to promote health and wellbeing and to achieve various learning goals. One such goal is promoting personal and social development to support students to value and lead a healthy and active lifestyle, especially during transition into adolescence. In order to design learning environments that support students' engagement in PE, it is important to understand how outcomes such as motor competence (MC) influence motivation for PE. There are two approaches to understand MC, actual and perceived MC, and both have implications for healthy lifestyles in childhood and adolescence. Therefore, this study examined associations of actual and perceived MC with young adolescents' motivation for PE. Method: A sample of 236 students 11–14 years of age ( M = 13.01, SD = .72) participated in the study. Assessments included actual MC (Körperkoordinations test for Kinder; KTK), perceived MC (self-administered form of the pictorial scale of Perceived Movement Skill Competence; PMSC) and motivation for PE (Perceived Locus of Causality Scale; PLOC). Polynomial regression with Response Surface Analyses were conducted to examine the influence of actual and perceived MC on motivation for PE. Findings: The results showed weak-to-moderate positive associations of actual and perceived MC with students' motivation for PE. Perceived MC explained about 12% of the variance of student's self-determined motivation towards PE. This effect was larger in students with lower levels of perceived MC compared to students with higher levels of perceived MC. Discussion: Taking into account that both actual and perceived MC are synergistically related but only perceived MC explains self-determined motivation, our results suggest that perceived MC is an important factor to consider when attempting to promote an active and healthy lifestyle. Using the developmental model of motor competence [Stodden et al. 2008 . "A Developmental Perspective on the Role of Motor Skill Competence in Physical Activity: An Emergent Relationship." Quest 60 (2): 290–306] and self-determination theory [Deci and Ryan 2000 . "The "What" and "Why" of Goal Pursuits: Human Needs and the Self-Determination of Behavior." Psychological Inquiry 11 (4): 227–268. doi:10.1207/S15327965PLI1104_01], we discuss the findings in relation to the importance of considering perceived MC as an explicit outcome in the PE curriculum. Conclusion: During early adolescence, PE programs should not only focus on teaching movement skills but also fostering perceived MC in order to promote motivation for PE, especially among students with lower levels of self-perception. For this, pedagogical approaches such as need supportive teaching derived from self-determination theory can be used to help students become competent, confident and motivated movers.